Chikungunya associated vulvitis: case report and literature review - Guimarães, Isabel Cristina Chulvis do Val; Grinceviciene, Svitrigaile; Fialho, Susana Cristina Aidé Viviani; Guimarães, Renata do Val; Calvet, Guilherme Amaral (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Chikungunya virus is spreading worldwide due to migration and globalization and could be presented with systemic and with unusual symptoms. Objective: To report a case of virus-transmitted infection detected in a woman during the gynecological examination at a vulvar clinic. Case report: A 73-year-old Caucasian woman attended a vulvar clinic because of dyspareunia and vulvar burning. Ulcers were observed on labia minora and perineum. A Chikungunya was diagnosed by seroconversion in paired specimens. She was prescribed prednisolone 40 mg once a day for 10 days. After oral steroid treatment, the woman had no body rashes or lesions on her genitals. Conclusion: This study emphasized that rare signs of unusual vulvitis with ulcers could be associated with Chikungunya infection.